First record of the seagrass-boring shipworm Zachsia sp. (Bivalve: Teredinidae) in natural and transplanted Enhalus acoroides (Hydrocharitaceae) rhizomes in tropical Southwest Pacific - Nenni Asriani; Rohani Ambo-Rappe; Mahatma Lanuru (Biodiversitas Journal of Biological Diversity, 2019)
Seagrass ecosystems are under threat worldwide. Seagrass transplantation is one restoration approach which is has been tried with uneven success. While transplantation methods and oceanographic parameters have been investigated in attempts to understand the factors affecting transplant survival rate and seagrass transplantation success, little attention has been paid to the possible impact of pests. We observed borer molluscs in a seagrass Enhalus acoroides both from natural bed and transplant area. This is thought to be the first record from Indonesian waters of these bivalve molluscs of the genus Zachsia, family Teredinidae, the only mollusc genus known to bore into seagrass rhizomes. In a further eleven E. acoroides shoots (average length 10.5cm) we found between one and four calcareous burrows 2mm to 5mm in diameter inside the rhizome. Further research is required to determine the species present and its distribution in Indonesian waters as well as the true ecological impact of Zachsia sp. on seagrasses.